Yield of dwarf tomatoes grown with a nutrient solution based on recycled synthetic urine. (February 2019) - Zabel, P.; Bornemann, G.; Tajmar, M.; Schubert, D.
Abstract: Extended human spaceflight missions require not only the processing, but also the recycling of human waste streams in bio-regenerative life support systems, which are rich in valuable resources. The Combined Regenerative Organic food Production ® project of the German Aerospace Center aims for recycling human metabolic waste products to produce useful resources. A biofiltration process based on natural communities of microorganisms has been developed and tested. The processed aqueous solution is, among others, rich in nitrogen present as nitrate. Nitrate is one of the main nutrients required for plant cultivation, resulting in strong synergies between the developed recycling process and plant cultivation. The latter is envisaged as the basis of future bio-regenerative life support systems, because plants do consume carbon dioxide, water and nutrients in order to produce oxygen, water, food and inedible biomass. This paper describes a series of plant cultivation experiments performed with synthetic urine processed in a bioreactor. The aim of the experiments was to investigate the feasibility of growing tomato plants with this solution. The results of the experiments show that such cultivation of tomato plants is generally feasible, but that the plants are less productive. The fruit fresh weight per plant is less compared to plants grown with the half-strength Hoagland reference solution. This lack in production is caused by imbalances of sodium, chloride, potassium, magnesium and ammonium in the solution gained from recycling the synthetic urine. An attempt on adjusting the produced bioreactor solution with additional mineral fertilizers did not show a significant improvement in crop yield.